Pengaruh Faktor Individu dan Sosial terhadap Perkembangan Wirausaha Sosial Berkelanjutan dengan Politik Sebagai Faktor Penentu - Latifah Hanum; Irwan Noor; Lestari Eko Wahyudi (Universitas Pendidikan Ganesha, 2023)
This research examines the role of social entrepreneurship in reducing dependency and socioeconomic inequalities amidst uncertainty, openness, and global competition. Social-political environmental factors are the focus of the study to understand their influence on the development of social entrepreneurship. Through a survey with questionnaires and analysis using the Smart PLS method, this research aims to provide new insights into the literature on social entrepreneurship and related values. The research findings reveal that the growth of social entrepreneurship aligns with the inability of the formal sector to absorb abundant labor. Individual, social, and political factors are crucial in developing Sustainable Social Entrepreneurship. Motivation, creativity, leadership, family support, social networks, community relationships, policies, and political regulations all influence the success of sustainable social entrepreneurship. However, regulatory barriers and bureaucracy can hinder the growth of social entrepreneurship. This study provides insights to policymakers for developing policies that support the development of social entrepreneurship. By understanding the importance of social-political environmental factors in the context of social entrepreneurship, sustainable and impactful social entrepreneurship can be fostered within society.